Influencia del arqueo en el suplex de los luchadores Categoría Menores. Federación Deportiva de Chimborazo, 2019 - Ferigra López, Abdon Israel (2019)
The objective of this research was to determine the influence of the arch in the back Suplex technique in the minor fighters of the Federación Deportiva de Chimborazo. In the study it worked with the entire sample in this case with 14 athletes of the minor category of the Olympic wrestling discipline, ten men corresponding to the 71.43% between 13 and 15 years and four women corresponding to the 28.57% between 14 and 15 years. Descriptive research was used, cross-sectional of quantitative type; the Gymnastic Arc test was applied as a research instrument to measure overall flexibility in gymnastics. Also, a Suplex Technique test was carried out; it was endorsed by technicians of the Olympic wrestling discipline of the Federación Deportiva de Chimborazo. The result showed in this research a low level in terms of the execution of the gymnastic arch with a 42.90% a Regular score, 28.60% was in the Good score, 21.40% a Very Good score and only 7.10% performed it in an Excellent way according to the Gymnastic Arc Test. It was found that in the execution of the Suplex Technique test, the ranking score is Very Good with 38.30% placing it in the middle part, 31.50% of the athletes perform it in an Excellent way. It also concluded that the Arch and the Suplex Technique correlate the first aid to the correct execution of the other.